Green Cities. - Keane, Adrienne; Davies, Peter (Palgrave Macmillan, 2020)
Green cities is a concept that explains a way to balance the needs of a city and the needs of the natural environment. This chapter demonstrates the interrelatedness between people and nature, that is a coupled human and natural system. The concept of a green city is based on understanding the ecosystem harm caused by urbanisation, and how this is compromising liveability and reconciling the impacts to bring about better ecosystem, people and built outcomes. Key to this is how people understand the urban ecosystem (environment as a public good; ecological literacy) and its role in supporting built and natural systems. The chapter concludes by illustrating how urban ecosystems can be supported through a vast array of actions at different scales – from a suburban garden to a whole city – and the use of technological approaches (green infrastructure).
Keywords: Stadtklima; Stadtgrün; Stadtplanung; Stadtnatur; Ökosystem; Ökosystemleistung; Grüne Infrastruktur